Innovative Atmospheric Plasma Jets for Advanced Nanomaterial Processing - Sabet, Maziyar (Journal of Research Updates in Polymer Science, 2024)
This study presents a comprehensive exploration of atmospheric pressure plasma jets (APPJs) as an innovative method for synthesizing and modifying nanomaterials, offering a versatile and efficient approach to tailoring their properties and functionalities. Unlike traditional low-pressure plasma techniques, APPJs operate at ambient conditions, providing significant advantages in scalability, cost-effectiveness, and environmental sustainability. This review delves into the recent advancements in APPJ technology, including the development of microfluidic configurations that enhance plasma generation and control, leading to improved efficiency, power, and user accessibility. These advancements have opened new possibilities in various fields, such as the development of antimicrobial coatings, advanced drug delivery systems, and high-performance solar cells. The ability of APPJs to facilitate precise surface engineering and targeted material deposition positions them as a transformative technology in nanomaterial processing. Despite their potential, challenges such as scalability and environmental impact must be addressed to realize widespread adoption. This study underscores the promise of APPJs in driving future industrial applications and highlights the need for continued innovation to overcome current limitations and unlock their full potential across multiple sectors.